Outside Back Cover: Biotechnology Journal 1/2020. Issue 1 (2nd January 2020) - Moço, Pablo D.; Aharony, Noga; Kamen, Amine
Abstract : Gene editing techniques, more specifically TALEN and CRISPR/Cas9, and transgene delivery with adeno‐associated virus serotype 6 are shaping the future of universal CAR‐T cell therapies. The deletion of the endogenous TCR and expression of target chimeric antigen receptor on T‐cells would allow access to off‐the‐shelf allogeneic CAR‐T cells for broad applications of cancer immunotherapies. This is reported by Pablo D. Moço, Noga Aharony, and Amine Kamen in article 1900286 . Cover design by David Sharon following an original idea by Pablo D. Moço